Five-Year Outcomes of Patients With Mitral Structural Valve Deterioration Treated With Transcatheter Valve in Valve Implantation – A Single Center Prospective Registry - Schamroth Pravda, Nili; Mishaev, Raffael; Levi, Amos; Witberg, Guy; Shapira, Yaron; Orvin, Katia; Barkan, Yeela Talmor; Hamdan, Ashraf; Sharoni, Ram; Perl, Leor; Sagie, Alexander; Assa, Hana Vaknin; et al. (Frontiers in Cardiovascular Medicine, 2022)
The Valve-in-Valve (ViV) technique is an emerging alternative for the treatment of bioprosthetic structural valve deterioration (SVD) in the mitral position. We report on intermediate-term outcomes of patients with symptomatic SVD in the mitral position who were treated by transcatheter mitral valve-in-valve (TM-ViV) implantation during the years 2010-2019 in our center. Three main outcomes were examined during the follow-up period: NYHA functional class, TM-ViV hemodynamic data per echocardiography, and mortality. Our cohort consisted of 49 patients (mean age 77.4+-10.5 years, 65.3% female). The indications for TM-ViV were mainly for regurgitant pathology (77.6%). All 49 patients were treated with a balloon-expandable device. The procedure was performed via transapical access in 17 cases (34.7%) and transfemoral vein / trans-atrial septal puncture in 32 cases (65.3%). Mean follow-up was 4.4 ± 2.0 years. 98% and 91% of patients were in NYHA I/II at 1 and 5 years respectively. Mitral regurgitation was ≥ moderate in 86.3% of patients prior to the procedure and this decreased to 0% (p<0.001) following the procedure and was maintained over 2 years follow-up. The mean trans-mitral valve gradients decreased from pre-procedural values of 10.1± 5.1mmHg to 7.0 ±2.4mmHg at one month following the procedure (p=0.03). Mortality at one year was 16% (95%, CI 5-26) and 35% (95%, CI 18-49) at 5 years. ViV in the mitral position offers an effective and durable treatment option for patients with SVD at high surgical risk.